Pelatihan Praktek Thaharah Mahasiswa KKP bersama Masyarakat Kelurahan Bontoramba Kabupaten Jeneponto - M. Amin, M. Amin; Mustari, Nuryanti; Nasra, Nasra; Sifa, Nurul (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
Thaharah practice training is an important activity in strengthening understanding of hygiene procedures in worship for Muslims. This research aims to explore the effectiveness of practical thaharah training involving Practical Work College (KKP) students with the community of Bontoramba Village, Jeneponto Regency. The training method used in this research uses a qualitative approach with a case study method. A qualitative approach was chosen because this research aims to understand in depth the implementation of thaharah practice training and its impact on people's knowledge and skills in purifying themselves. Through a series of activities such as demonstrations, group discussions and direct practice, KKP students work together with the community in practicing thaharah procedures in accordance with the teachings of the Islamic religion. This research aims to provide understanding and skills for students and the community after attending the training. It is hoped that the results of this research will provide valuable insight into the effectiveness of thaharah practice training in the context of KKP student participation and interaction with the community, as well as highlight the importance of a collaborative approach in strengthening understanding of religion and hygiene practices in the community.